2017
DOI: 10.3390/ijms18112325
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Effects on Wound Healing

Abstract: Wound healing is a physiological process, involving three successive and overlapping phases—hemostasis/inflammation, proliferation, and remodeling—to maintain the integrity of skin after trauma, either by accident or by procedure. Any disruption or unbalanced distribution of these processes might result in abnormal wound healing. Many molecular and clinical data support the effects of estrogen on normal skin homeostasis and wound healing. Estrogen deficiency, for example in postmenopausal women, is detrimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
93
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 141 publications
(96 citation statements)
references
References 104 publications
(241 reference statements)
2
93
0
1
Order By: Relevance
“…In particular, the roles of platelets in the development of endometriosis has been demonstrated only recently 23 , despite the disease is characterized conspicuously by cyclic bleeding 55 . Indeed, estrogen is very important to wound healing 27,28 and so is ERβ 37,38 in wound healing, another similarity that cannot be dismissed as just a pure coincidence. In essence, this study shows that, as wounds undergoing ReTIAR, platelets also participate in the increased local production of estrogens through various ways.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In particular, the roles of platelets in the development of endometriosis has been demonstrated only recently 23 , despite the disease is characterized conspicuously by cyclic bleeding 55 . Indeed, estrogen is very important to wound healing 27,28 and so is ERβ 37,38 in wound healing, another similarity that cannot be dismissed as just a pure coincidence. In essence, this study shows that, as wounds undergoing ReTIAR, platelets also participate in the increased local production of estrogens through various ways.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings give more credence to the notion that endometriotic lesions are wounds undergoing ReTIAR. Indeed, peripheral tissues produce estrogens 71 , and estrogens play a vital role in wound healing 27,28 . While normal endometrial stromal cells only produce negligible levels of estrogens 41 likely due to a silenced aromatase because of hypermethylation 41,42 , endometriotic stromal cells, in contrast, do produce a much higher level of estrogens, www.nature.com/scientificreports www.nature.com/scientificreports/ due to demethylated aromatase 42 , and overexpression of StAR, HSD3B2 and HSD17B1 12,43,45,47 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies have shown that sex [41] and the levels of sex hormones have an impact on woundhealing potential. Oestrogen is thought to stimulate healing, and testosterone to induce it [47].…”
Section: Factors That Delay Wound Healing and Influence Scar Outcomementioning
confidence: 99%